Strategi Pelestarian Budaya dan Alam untuk Pariwisata Berkelanjutan: Studi Kasus Kampung Adat Banceuy, Subang, Jawa Barat - Bahreisy, Afghani Mahmuda; Siswhara , Gita (Sekolah Tinggi Pariwisata Sahid Surakarta, 2025)
Kampung Adat Banceuy, located in Subang Regency, is one of the indigenous communities that continues to uphold traditional values and environmental conservation amidst the currents of modernization and tourism development. This study aims to explore the strategies for cultural and environmental preservation undertaken by the indigenous community, tourism village managers, Pokdarwis (Tourism Awareness Groups), and the role of tourists in supporting sustainable tourism. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving various stakeholders in Kampung Adat Banceuy. The findings reveal that preservation is carried out through the intergenerational transmission of customary values, community-based ecotourism management, and the implementation of local regulations for environmental protection. Collaboration among indigenous communities, tourism managers, and tourists emerges as a key factor in developing a sustainable tourism model. The study recommends strengthening customary institutions and enhancing community capacity in managing tourism in line with conservation principles.